Adat Penti Orang Manggarai dalam Global Village - Hironimus Bandur (Jurnal Alternatif Wacana Ilmiah Interkultural, 2012)
The Process of globalization has been invading almost all aspect of human life which force ordinary Indonesian people to come to terms with this global movement. The notion of diversity is very strong among Indonesiansand eventually considered as an internal power to deal with the diversifed society. Hoever, not every Indonesian seems to grasp and live this variety or the dynamic of differences as a blessing. This article is showing us the necessity of an inculturation and that Inculturation or contextualization is deeper than adaptation.The author has smartly taken into account the importance of a fundamental rite by the Manggaraians and have it met vigorously with the catholicreligion.The authoris notabsentto putthe analogicalimagination in the whole procedure of this encounter.The author even promotes tha multicultural education as desperatelyneeded. Meanwhile, the implementation of this kind of education needs cooperation between all elements in Manggarai.The process of Inculturation of course needs a local base as “locus theologicus".